A falusi település térbelisége a lakosság térpályái alapján - Mészáros, Rezső (Tér és Társadalom, 1988)
Each stage of socio-economic development establishes its own spatial category (or spatial size) which provides frameworks for the basic processes at the given stage. This spatial development is widely analysed by scientists as a result of which various spatial categories ,have been produced: economic regions, attraction zones, agglomerations, urban regions, local areas etc. As a matter of fact each of them is a physical spatial unit, either structured or homogeneous, delimited according to certain criteria. Their most important elements are the settlements. Spatial categories can be described in geography by the horizontal extent of inter-settlement interactions. The spatial interactions of a settlement cannot be, however, reduced to its external, inter-settlement, relationships. The population of each settlement delimits and partly or fully fills in an area by its movements in certain directions with given intensity and with some objectives. This areas receives its functional content from the people’s activities; the individual moves within this area to activate its functions. The above mentioned analyses of spatial categories paid little attention to the mechanism of how the directions of streams (spatial paths) made of people’s spatial movements develop and how they exert their impacts. It may be justified to find an answer to the question what is the scope like which a settlement provides for its inhabitants or how does the lack of its functions confine the inhabitants’ scope of activities. It is interesting to learn about the time structure of these streams, namely, how their directions and distances change over time (daily, weekly, monthly). Would this all express the content and size of a settlement’s spatial dimension in a satisfactory manner? In order to solve the tasks condensed in the above questions, a survey was initiated in five villages. The present paper contains the major results of the survey conducted in Bócsa, a Hungarian village, on the basis of which it is exptected that further analyses would confirm the following statements: the spatial dimension of a rural settlement can be interpreted by the spatial form that results from the totality of population streams. This is a variable form that follows the rythm of the spatial moves of the population. In certain periods, as the centre of gravity of the directions changes, it either expands beyond the static administrative area of the settlement or remains within that; knowing the content and the time structure of spatial streams brings us closer to the understanding of the basic spatial structure of the territorial division of labour; the inter-settlement interaction system as revealed by population streams provides important new information for the better understanding of how settlement hierarchy operates.